An optimized sliding‐mode observer control algorithm for vehicle sensor‐less PMSM. Issue 3 (17th March 2023) - Jingbo, Wu; Chengwei, Xie; Zhijun, Guo; Yongwei, Wang
Abstract: An optimized sliding‐mode observer control algorithm for permanent magnet synchronous motor (PMSM) is proposed to solve the problems in the conventional sliding‐mode observer control algorithms (e.g., system chattering and phase delay). The proposed algorithm adopts a new piecewise function as a switching function to reduce system chattering. The low pass filter in the conventional sliding‐mode observer is substituted with a complex coefficient filter in the proposed algorithm to solve the phase delay caused by the low pass filter. Moreover, the counter emf back obtained using the filtering of the complex coefficient filter is reintroduced into the sliding‐mode observer to decrease the sliding‐mode gain coefficient and reduce chattering in the system. the simulation results suggest that the proposed algorithm outperforms the conventional sliding‐mode observer control algorithm in reducing chattering, increasing the convergence speed, reducing torque pulsation, increasing speed estimation accuracy and coping with speed and load mutation. Abstract : The proposed algorithm adopts a new piecewise function as a switching function to reduce system chattering. The low pass filter in the conventional sliding‐mode observer is substituted with a complex coefficient filter in the proposed algorithm to solve the phase delay caused by the low pass filter. Moreover, the counter emf back obtained using the filtering of the complex coefficient filter is reintroduced into the sliding‐mode observer to decrease the sliding‐mode gain coefficient and reduce chattering in the system.